Trends in the Prevalence of Hypertension and Type 2 Diabetes in Bangladesh (2010-2020): A Systematic Review and Meta-Analysis - Hoq, Mohammad I.; Hossain, Mohotasin; Jahan, Shamima; Mahmud, Hasan; Akter, Farjana; Mahmud, Faisal; Uddin, Main; Siddiqui, Shafayet Ahmed; Jakaria, M.D. (Current Diabetes Reviews, 2023)
Background: The prevalence of cardiovascular diseases (CVDs) and type 2 diabetes mellitus (T2DM) has increased in Bangladesh. This paper has reviewed published studies on hypertension and T2DM from 2010 to 2020 in Bangladesh and conducted a meta-analysis. Methods: The PubMed database was used for systematic search. Hypertension and T2DM were considered for measuring pooled prevalence by meta-analysis. The random-effects model was used to calculate the pooled prevalence of hypertension (n = 30) and T2DM (n = 21) in relevant studies. The quality of the reviewed studies was determined by sampling strategy, sample size, and outcome assessment. The meta-analysis protocol was registered at PROSPERO (CRD42020206315). Results: The pooled hypertension and T2DM prevalence was 21.6% (95% CI: 18.8%-24.4%) and 13.6% (95% CI: 10.8%-16.5%), respectively. Females were more hypertensive than males (M vs. F: 18.6% vs. 24.8%), and T2DM was higher in females (M vs. F: 12.4% vs. 13.3%). Urban dwellers were more hypertensive and diabetic than rural people (urban vs. rural: 28.5% vs. 20.3% and 18.8% vs. 14.2%, respectively). An 8% increase in the prevalence of hypertension and T2DM became more than double compared to the 1995-2010 period. Conclusion: Future research should focus on the underlying factors that increase the prevalence of these diseases and prevention strategies to reduce the trend of increasing prevalence.
Keywords: Hypertension